1980
DOI: 10.3109/10826088009040051
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Phobic Disorders in Methadone Maintenance Treated Patients

Abstract: A detoxification phobia idiosyncratic to methadone maintenance programs is described and several representative cases are presented. Reliability of diagnostic criteria for the phobia are described and their overall reliability was found to be 93% while occurrence reliability was 67%, which investigators conclude is a moderate but clinically useful level. Prevalence data show the phobia occurring in 27% of a random sample of patients treated with methadone maintenance, an estimate the investigators feel is too … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…High anxiety and fear about the withdrawal experience often lead to treatment drop-out and relapse. Thus, in this first iteration of the ACT treatment for methadone detoxification we chose to target detoxification fear (Milby et al, 1980; Milby et al, 1994), as well as the ACT-based mechanisms of avoidance and inflexibility in responding in the presence of negative private events. Results suggested that our ACT treatment differentially impacted detoxification fear relative to DC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High anxiety and fear about the withdrawal experience often lead to treatment drop-out and relapse. Thus, in this first iteration of the ACT treatment for methadone detoxification we chose to target detoxification fear (Milby et al, 1980; Milby et al, 1994), as well as the ACT-based mechanisms of avoidance and inflexibility in responding in the presence of negative private events. Results suggested that our ACT treatment differentially impacted detoxification fear relative to DC.…”
Section: Discussionmentioning
confidence: 99%
“…In 1980, Milby and his colleagues (1980) identified among methadone maintenance clients an “iatrogenic detoxification phobia,” which can be reliably detected and was present in almost 30% of the sample examined. Prevalence rates in the general methadone maintenance (MM) population may be even higher as severely phobic clients are less likely to enter detoxification programs.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently the abstinence fear was activated when the patients were reminded of its existence by being forced to make a more concrete decision in the questionnaire. Several studies have shown that an exaggerated fear of abstinence is common among methadone patients [23][24][25][26][27]. Table 1 shows that nearly no differences existed with respect to social background conditions or the drug use of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…ification (Cushman & Dole, 1973). A detoxification phobia that met DSM-I1 diagnostic criteria prevented rehabilitated patients from initiating detoxification (Milby, Garrett, & Meredith, 1980). Several other studies have documented the presence or effects of detoxification fear (Hall, 1979;Hall, Loeb, & Kushner, 1984;Hirt & Greenfield, 1979;Milby, Rice, & Garrett, 1979).…”
mentioning
confidence: 99%
“…On the pathological side are preoccupation with intense or bizarre physical symptoms and certain failure to withdraw with fear of consequent arrest and/or other dire consequences. Most pathological is a phobia of detoxification found among clients who become intensely anxious at the suggestion of detoxification and avoid it in spite of the fact that they meet rehabilitation criteria (Milby et al, 1980).…”
mentioning
confidence: 99%